In-hospital major bleeding in patients with acute coronary syndrome medically treated with dual anti-platelet therapy: Associated factors and impact on mortality - Sun, Yihong; Feng, Lin; Li, Xian; Wang, Zhe; Gao, Runlin; Wu, Yangfeng (Frontiers in Cardiovascular Medicine, 2022)
Objective Major bleeding is associated with poor hospital prognosis in patients with acute coronary syndrome (ACS). Despite its clinical importance, there are limited studies on the incidence and risk factors for major bleeding in ACS patients with dual anti-platelet therapy (DAPT) without access to revascularization. Methods We analyzed data from 19,186 patients on DAPT after ACS with no access to revascularization from Clinical Pathway for Acute Coronary Syndrome in China Phase 3 (CPACS-3) cohort, which was conducted from 2011 to 2014. Major bleeding included intracranial hemorrhage, clinically significant bleeding, or bleeding requiring blood transfusion. Factors associated with in-hospital major bleeding were assessed using Poisson regressions with generalized estimating equations to account for the clustering effect. Results A total of 75 (0.39%) patients experienced major bleeding during hospitalization. Among subtypes of ACS, 0.65% of patients with STEMI, 0.33% with NSTEMI, and 0.13% with unstable angina had in-hospital major bleeding (p < 0.001). The patients who experienced major bleeding had a longer length of stay (median 12 vs. 9 days, p = 0.011) and a higher all-cause in-hospital death rate (22.7 vs. 3.7%, p < 0.001). Multivariable analysis showed advancing age (RR = 1.52 for every 10 years increase, 95% CI: 1.13, 2.05), impaired renal function (RR = 1.79, 95% CI: 1.10, 2.92), use of fibrinolytic drugs (RR = 2.93, 95% CI: 1.55, 5.56), and severe diseases other than cardiovascular and renal diseases (RR = 5.56, 95% CI: 1.10, 28.07) were associated with increased risk of major bleeding, whereas using renin–angiotensin system inhibitors (RR = 0.54, 95% CI: 0.36, 0.81) was associated with decreased risk of major bleeding. These independent factors together showed good predictive accuracy with an AUC of 0.788 (95% CI: 0.734, 0.841). Conclusion Among ACS patients on DAPT, advancing age, impaired renal function, thrombolytic treatment, and severe comorbidities were independently associated with a higher risk of in-hospital major bleeding.